Cascas de algodão e de soja e farelos de gérmen de milho ou de arroz na alimentação de novilhas mestiças : desempenho, digestibilidade aparente e composição físico-química do músculo Longissimus Dorsi - Kazama, Ricardo (2006)
It was aimed to evaluate ruminal degradability of some agroindustrial by-products, apparent digestibility of diets, animal performance, carcass characteristics, physico-chemical composition and fatty acids composition of Longissimus dorsi muscle from feedlot crossbred heifers fed with rations with cottonseed hulls (CSH) and soybean hulls (SBH) as roughages, and with different energy sources: ground corn (COR), corn germ meal (CGM) or rice bran (RIB). Three Holstein steers, each fitted with a ruminal cannula and weighing 400 ± 64 kg, were used for ruminal degradability trial. Twenty-four crossbred heifers were allocated in a completely randomized design with three treatments for the determination of diet apparent digestibility, animal performance, carcass characteristics and Longissimus dorsi (LD) analysis. Regarding roughage feeds, CSH presented slower ruminal degradation than SBH. RIB and CGM presented higher dry matter (DM) and crude protein (CP) effective degradability (5%/h) than COR. There wasn't any difference (P>0.05) among heifers fed different experimental rations in DM intake (10.32 kg/day) and other nutrients, exception to ether extract (EE) intake, which was higher for CGM and RIB rations (0.41 kg/day) in relation to COR ration (0.25 kg/day). CGM ration presented higher apparent digestibility coefficient of DM, CP and EE when compared to COR ration. The performance of feedlot heifers didn't differ (P>0.05) among rations with COR, CGM or RIB, presenting an average daily gain of 1.23 kg/day and feed conversion of 8.45 kg of DM/kg of gain. There wasn?t any difference (P>0.05) among animals in carcass characteristics and physico-chemical compositions of LD. Fatty acids composition of LD were modified on heifers fed CGM ration and presented higher concentrations of CLA (0.48%), trans-vaccenic acid (7.69%) but worse omega3/omega6 ratio, and heifers fed RIB ration presented higher concentration of stearic acid in the muscle. These agroindustrial by-products can be used on diets for feedlot heifers because they didn't modify animal performance, carcass characteristics and meat quality.